Os tempos e espaços do gestor escolar em formação na educação a distância - Aline Gabriele Pereira (2013)
The importance of continuing education for educational worker is known, and through Distance Education (DE) conducting such formation without the need for time off work became even more "viable" and common without, however, considering the implications of such formation in work and life of these subjects. The Specialization Course in School Management, part of the National Program College of Managers of Basic Education, established by the Ministry of Education, is one such example, providing to managers of public schools throughout Brazil continuing education lato sensu trough distance education, and will be the focus of this research, which seeks to analyze the time and space used by these school managers in conducting this formation. Thereunto the survey was conducted among the students egresses from the course offered by UFMG in 2008 and 2010. We analyzed data obtained from the questionnaires of 260 subjects and semi-structured interviews conducted with 15 of them. The data resulting from the research are spread over three chapters, in which will be treated: the configuration of the Specialization Course in School Management and how it was implemented; the factors that facilitate and/or hinder the achievement of continuing education in distance learning mode; the work of school management and the particularities of being a mostly female work; and the relationship between work time and free time. The analysis was performed in order to deepen the understanding of time and space used by these managers in conducting the formation, understanding them beyond mere choice of the subjects, as representations of the social context to which they belong.